Earlier In Vitro Viral Production With SARS-CoV-2 Alpha Than With Beta, Gamma, B, or A.27 Variants - Lebourgeois, Samuel; Chenane, Houssem Redha; Houhou-Fidouh, Nadhira; Menidjel, Reyene; Ferré, Valentine Marie; Collin, Gilles; Benmalek, Nabil; Coppée, Romain; Larrouy, Lucile; Yazdanpanah, Yazdan; Timsit, Jean-François; Charpentier, Charlotte; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Since its emergence in China at the end of 2019, SARS-CoV-2 has rapidly spread across the world to become a global public health emergency. Since then, the pandemic has evolved with the large worldwide emergence of new variants, such as the Alpha (B.1.1.7 variant), Beta (B.1.351 variant), and Gamma (P.1 variant), and some other under investigation such as the A.27 in France. Many studies are focusing on antibody neutralisation changes according to the spike mutations, but to date, little is known regarding their respective replication capacities. In this work, we demonstrate that the Alpha variant provides an earlier replication in vitro, on Vero E6 and A549 cells, than Beta, Gamma, A.27, and historical lineages. This earlier replication was associated with higher infectious titres in cell-culture supernatants, in line with the higher viral loads observed among Alpha-infected patients. Interestingly, Beta and Gamma variants presented similar kinetic and viral load than the other non-Alpha-tested variants.